Long-Term Ibrutinib Therapy Reverses CD8+ T Cell Exhaustion in B Cell Chronic Lymphocytic Leukaemia - Parry, Helen M.; Mirajkar, Nikhil; Cutmore, Natasha; Zuo, Jianmin; Long, Heather; Kwok, Marwan; Oldrieve, Ceri; Hudson, Chris; Stankovic, Tatjana; Paneesha, Shankara; Kelly, Melanie; Begum, Jusnara; et al. (Frontiers in Immunology, 2019)
Chronic Lymphocytic Leukaemia (CLL) is associated with immune suppression and susceptibility to infection. CD8+ T cell numbers are increased and demonstrate elevated expression of PD-1 and impaired function. The mechanisms driving these features of exhaustion are uncertain but are likely to include chronic immune recognition of tumor and/or infectious agents. We investigated the number, phenotype and function of total and virus-specific CD8+ T cells in 65 patients with CLL and 14 patients undergoing long-term ibrutinib therapy (median 21 months). Ibrutinib substantially reduced the number of both CD3+ T cells and CD8+ T cells. Importantly, this was associated with a reduction in PD-1 expression on CD8+ T cells (median 28% vs 24%; p=0.042), stable cytotoxic activity and 3.5 fold increase in cytokine production following mitogen stimulation. The influence of ibrutinib on antigen-specific CD8+ T cell function was assessed by HLA-peptide tetramers and revealed increased IFN and TNF cytokine responses following stimulation with CMV or EBV peptides together with a 55% reduction in the number of ‘inflated’ virus-specific CD8+ T cells. These findings reveal that long-term ibrutinib therapy is associated with substantial reversal of T cell exhaustion in B-CLL and is likely to contribute to the reduced infection risk seen in association with this agent.